The role of biotechnology in animal agriculture to address poverty in Africa: Opportunities and challenges. Proceedings of the 4th all Africa conference on animal agriculture and the 31st annual meeting of the Tanzania Society for Animal Production - Tanzania Society for Animal Production (Tanzania Society for Animal Production, 2006)
The overall objective of the conference was to provide an opportunity for African scientists and the broader stakeholder groups of the livestock sector to discuss the potential role of biotechnology in animal agriculture to improve the livelihoods of African people. The conference aimed to attempt, through discussions of a series of papers, to answer the questions: Is biotechnology a menace or an opportunity to address the pressing needs for sustainable livelihoods of poor people? What are the potentials and limitations/threats of biotechnology? The conference is organized in eight chapters. These are - "Ecosystems and Ecosystem Services"; "Spatial Patterns of Poverty and Human Well-Being", "Water" (water supply and demand, water based ecosystem services, and water as a hazard - flooding); "Food" (Food and livelihoods, food crops: major supply areas, livestock products, and food from the wild); "Biodiversity" (Selected indicators of biodiversity, how people affect Kenya's biodiversity, and losing and gaining); "Tourism (Links between ecosystem services and tourism, key ecosystem assets for the tourism sector, and nature-based tourism: infrastructure, visitor and revenue trends, and spatial diversification); "Wood" (Overall distribution of woody biomass, and key supply areas for firewood and charcoal); and "The Upper Tana: Patterns of Ecosystem Services and Poverty".